All-solid-state battery

CN122996533APending Publication Date: 2026-10-27LG ENERGY SOLUTION LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202580022119.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-12-26
Filing Date
2025-12-26
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

但该类无阳极全固态电池需要额外的金属涂覆和溅射工序,使得成本增加

Benefits of technology

[0029]本发明可以提供具有改善的放电容量和循环特性的无阳极全固态电池。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122996533A_ABST
    Figure CN122996533A_ABST
Patent Text Reader

Abstract

The present invention aims to provide an anode-free all-solid-state battery having improved discharge capacity and cycle characteristics. Furthermore, the present invention aims to provide an anode-free all-solid-state battery capable of being driven at a low constraint pressure. The all-solid-state battery provided by the present invention includes: a positive electrode including a positive electrode active material layer; a negative electrode current collector; and a solid electrolyte layer provided between the positive electrode and the negative electrode current collector, wherein the all-solid-state battery does not contain a negative electrode active material, wherein lithium ions are supplied from the positive electrode active material layer by charging, thereby forming a lithium metal layer as a negative electrode active material on the negative electrode current collector, and the solid electrolyte layer contains a sulfide-based solid electrolyte containing a Group 12 element and having a sulfosalt-type crystal structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an all-solid-state battery with an anode-free structure.

[0002] This application is based on and claims priority to Japanese Patent Application No. 2024-231223, filed with the Japan Patent Office on December 26, 2024, the disclosure of which is incorporated herein by reference in its entirety. Background Technology

[0003] To achieve higher safety, longer lifespan, and higher energy density, all-solid-state batteries have been developed that use solid electrolytes instead of liquid electrolytes in lithium-ion batteries. Among various solid electrolytes, sulfide solid electrolytes (such as Li-ion batteries) are particularly popular. 10 GeP2S 12 Sulfide-based solid electrolytes have high ionic conductivity comparable to liquid electrolytes, and due to their flexibility, they can easily form close contact with active materials. Therefore, all-solid-state batteries using sulfide-based solid electrolytes are expected to be commercialized.

[0004] Lithium metal has attracted widespread attention as an anode material for all-solid-state batteries due to its low mass per unit volume, high theoretical capacity, and ability to improve gravimetric energy density (Wh / kg). However, sulfide solid electrolytes (such as Li...) 10 GeP2S 12 It has poor stability with lithium metal and is difficult to use with lithium metal anodes.

[0005] Furthermore, when lithium metal is used as the negative electrode in a battery, the battery is typically manufactured by bonding lithium foil onto a planar current collector. However, lithium is a highly reactive alkali metal, reacting violently with water and oxygen in the air, making it difficult to manufacture and use under normal conditions. Especially when lithium metal is exposed to the atmosphere, it oxidizes to form LiOH, Li₂O, or Li₂CO₃ oxide films. When an oxide film is present on the surface, it acts as an insulating layer, reducing conductivity, hindering the rapid migration of lithium ions, and leading to increased resistance.

[0006] To address this issue, Patent Documents 1 to 3 disclose an anode-free all-solid-state battery, characterized by depositing a small amount of seed metal (e.g., Ag or Zn) that alloys with lithium on the negative electrode current collector. However, this type of anode-free all-solid-state battery requires additional metal coating and sputtering processes, increasing costs. Furthermore, to suppress lithium dendrite growth, this anode-free all-solid-state battery requires high confinement pressure during operation.

[0007] To address the aforementioned issues, the inventors, through in-depth research, designed an anode-free all-solid-state battery. After battery assembly, during charging, lithium ions migrating from the positive electrode active material form a lithium metal layer on the negative electrode current collector, thus preventing lithium metal from contacting the atmosphere during battery assembly. Furthermore, the anode-free all-solid-state battery developed by the inventors uses a sulfide-based solid electrolyte containing multivalent cations as the solid electrolyte to improve discharge capacity and cycle characteristics, and enables operation under low confinement pressure.

[0008] Existing technical documents

[0009] Patent documents

[0010] Patent Document 1: Japanese Patent Publication No. 2020-191202

[0011] Patent Document 2: Japanese Patent Publication No. 2020-167146

[0012] Patent Document 3: Japanese Patent Publication No. 2022-504134

[0013] Patent Document 4: Japanese Patent Publication No. 2022-529975 Summary of the Invention

[0014] Technical issues

[0015] The present invention aims to provide an anode-free all-solid-state battery with improved discharge capacity and cycle characteristics.

[0016] The present invention also aims to provide an anode-free all-solid-state battery that can operate under low constraint pressure.

[0017] Technical solution

[0018] To achieve the above objectives, the present invention provides: An all-solid-state battery comprising: The all-solid-state battery comprises a positive electrode with a positive active material layer, a negative current collector, and a solid electrolyte layer disposed between the positive electrode and the negative current collector, wherein the all-solid-state battery does not contain a negative active material. During charging, lithium ions are supplied from the positive electrode active material layer to form a lithium metal layer serving as the negative electrode active material on the negative electrode current collector. The solid electrolyte layer comprises a sulfide solid electrolyte containing elements of Group 12, and the sulfide solid electrolyte has a sulfogermanium ore-type crystal structure.

[0019] In one embodiment, the negative electrode current collector and the solid electrolyte layer can be in direct contact.

[0020] In one embodiment, the sulfide-based solid electrolyte can be made of chemical formula Li 7-x-2y M y PS 6-x Ha x express, In the above chemical formula, M is at least one element selected from Group 12. Ha is at least one element selected from halogen elements. 0 <x<2 . 5,0 <y<0 . 45.

[0021] In one implementation, M can be Zn.

[0022] In one embodiment, the all-solid-state battery may be free of the reaction products between the negative electrode current collector and the sulfide-based solid electrolyte.

[0023] In one embodiment, a 0°C pressure can be applied to the all-solid-state battery along the stacking direction of the positive electrode, the negative electrode current collector, and the solid electrolyte layer. . Pressure below 3 MPa.

[0024] In one embodiment, the positive electrode active material layer may contain the sulfide-based solid electrolyte.

[0025] In one embodiment, the D10 of the solid electrolyte can be 0. . 1 μm to 10 μm.

[0026] In one embodiment, the D50 of the solid electrolyte can be 0. . 1 μm to 50 μm.

[0027] In one embodiment, the D90 of the solid electrolyte can be from 1 μm to 100 μm.

[0028] Beneficial effects

[0029] This invention can provide an anode-free all-solid-state battery with improved discharge capacity and cycle characteristics.

[0030] Furthermore, the present invention can provide an anode-free all-solid-state battery capable of operating under low constraint pressure. Attached Figure Description

[0031] Figure 1 This is a schematic diagram of the all-solid-state battery in Example 1.

[0032] Figure 2 This is a schematic diagram of the all-solid-state battery in Comparative Example 1.

[0033] Figure 3 This is a schematic diagram of the all-solid-state battery in Comparative Example 2.

[0034] Figure 4 X-ray diffraction (XRD) patterns of fine-particle and coarse-particle solid electrolytes.

[0035] Figure 5 The graph shows the discharge capacity retention rate of the all-solid-state batteries of Example 1, Comparative Example 1, and Comparative Example 2. Detailed Implementation

[0036] The present invention will be described in more detail below.

[0037] It should be understood that the terms or words used in this specification and the appended claims should not be construed as limited to their general or dictionary meanings; rather, based on the principle that the inventor can appropriately define the concepts of terms in order to describe them in the best manner, they should be interpreted according to their meanings and concepts consistent with the technical solutions of this invention.

[0038] In the accompanying drawings, irrelevant details have been omitted for clarity, and the same elements throughout the text are indicated by the same reference numerals. Furthermore, the dimensions and relative sizes of the elements shown in the drawings are not proportional to actual scale and may be reduced or enlarged for clarity.

[0039] In this specification, "Dn" refers to the particle size distribution at the n% point of the cumulative particle size distribution. Specifically, D50 is the particle size (median particle size, average particle size) at the 50% point of the cumulative particle size distribution, D90 is the particle size at the 90% point, and D10 is the particle size at the 10% point. Particle size distribution can be determined using laser diffraction. Specifically, powder is dispersed in a dispersion medium and introduced into a commercially available laser diffraction particle size analyzer (e.g., Microtrac S3500). The particle size distribution is calculated by measuring the differences in diffraction patterns produced when particles of different sizes pass through a laser beam.

[0040] All-solid-state batteries

[0041] The all-solid-state battery of the present invention comprises: a positive electrode having a positive active material layer, a negative current collector, and a solid electrolyte layer disposed between the positive electrode and the negative current collector. The all-solid-state battery of the present invention does not contain a negative active material, and during charging, lithium ions are supplied from the positive active material layer to form a lithium metal layer serving as the negative active material on the negative current collector. In the all-solid-state battery of the present invention, the solid electrolyte layer may contain a sulfide-type solid electrolyte containing a Group 12 element, and the sulfide-type solid electrolyte has a sulfide-germanium sulfide crystal structure. With the above construction, the anode-free all-solid-state battery of the present invention can have improved discharge capacity and cycle characteristics. Furthermore, with the above construction, the anode-free all-solid-state battery of the present invention can operate under lower confinement pressure.

[0042] The term "all-solid-state battery" as used in this specification refers to an all-solid-state battery in its precursor state (referred to as the all-solid-state battery precursor) before lithium metal is deposited on the negative electrode current collector during the first cycle (first charge).

[0043] All-solid-state batteries can be all-solid-state lithium rechargeable batteries.

[0044] To prevent short circuits between the positive and negative electrodes that may be caused by lithium dendrite growth, all-solid-state batteries require confinement pressure during charging and discharging. This confinement pressure can be applied along the stacking direction of the positive and negative current collectors, as well as the solid electrolyte layer positioned between the positive and negative current collectors (i.e., perpendicular to the plane of the negative current collector). For example, confinement pressure can be applied by using clamps to secure the all-solid-state battery from both the positive and negative current collector sides.

[0045] To suppress lithium dendrite growth, all-solid-state batteries typically require high confinement pressure. However, this invention utilizes an all-solid-state battery with a sulfide-based solid electrolyte containing divalent cations, which requires only low confinement pressure or no confinement pressure at all.

[0046] During charging and discharging, 0 can be applied to the all-solid-state battery. . Below 3 MPa, preferably 0 . Below 1 MPa, more preferably 0 . Below 0.05 MPa, or even more preferably 0. . Pressure below 0.2 MPa. As described above, the anode-free all-solid-state battery of the present invention can operate under low constraint pressure.

[0047] Typically, the negative electrode of a lithium-ion secondary battery is formed on a negative electrode current collector. However, in the all-solid-state battery of this invention, the surface of the negative electrode current collector does not have metal particles or a coating layer; after assembling an anode-free battery structure using only the negative electrode current collector, lithium ions are driven to detach from the positive electrode active material during charging, thereby forming a lithium metal layer on the negative electrode current collector as the negative electrode active material. As a result, a negative electrode with the same structure as a conventional lithium-ion secondary battery, comprising a negative electrode current collector / negative electrode active material layer, can be formed.

[0048] That is, the concept of "anode-free battery" in this invention includes anode-free batteries in which no negative electrode is formed on the negative electrode current collector during initial assembly, as well as batteries in which a negative electrode is formed on the negative electrode current collector during cycling. However, the all-solid-state battery of this invention does not exclude the case where there are metal particles or a coating layer on the surface of the negative electrode current collector during initial assembly.

[0049] Furthermore, in the negative electrode of the present invention, the lithium metal present on the negative electrode current collector as the negative electrode active material includes lithium metal arranged in a layered structure and lithium metal arranged in a non-layered structure (e.g., agglomerated particle structure).

[0050] The following description is based on lithium metal layers containing a layered structure, but it is clear that the present invention does not exclude lithium metals that are not arranged in a layered structure.

[0051] <Solid Electrolyte Layer>

[0052] The solid electrolyte layer contains a solid electrolyte. In all-solid-state lithium secondary batteries, the solid electrolyte layer serves as insulation and an ion conduction channel.

[0053] The thickness of the solid electrolyte layer can be approximately 50 μm or less, preferably approximately 15 μm to 50 μm. The thickness can be appropriately determined within the above range, taking into account ionic conductivity, physical strength, or the energy density of the battery to which it is applied. For example, in terms of ionic conductivity or energy density, the thickness can be 10 μm or more, 20 μm or more, or 30 μm or more; in terms of physical strength, the thickness can be less than 50 μm, less than 45 μm, or less than 40 μm. Furthermore, in addition to the above thickness range, the solid electrolyte layer can also have a thickness of approximately 100 kgf / cm². 2 Approximately 2000 kgf / cm 2 The tensile strength is high. Meanwhile, the porosity of the solid electrolyte layer can be less than 15% by volume, or less than about 10% by volume. As described above, the solid electrolyte layer of the present invention has a small thickness but high mechanical strength.

[0054] (Solid electrolyte)

[0055] The solid electrolyte may include at least one of sulfide-based solid electrolytes, oxide-based solid electrolytes, or polymer-based solid electrolytes. Preferably, the solid electrolyte in the all-solid-state battery of the present invention is a sulfide-based solid electrolyte. The solid electrolyte may be contained in the positive electrode active material layer or in the solid electrolyte layer that acts as a separator.

[0056] The average particle size of solid electrolytes can be controlled according to requirements. Controlling the average particle size of solid electrolytes can improve ionic conductivity.

[0057] The average particle size of solid electrolytes can be controlled by changing conditions such as the ball mill speed and time, thereby producing coarse solid electrolytes with a larger average particle size and fine solid electrolytes with a smaller average particle size.

[0058] The average particle size D50 of solid electrolytes can be 0. . From 1 μm to 50 μm, D10 can be 0. . The average particle size (D50) of the coarse-particle solid electrolyte can be greater than that of the fine-particle solid electrolyte. The average particle size of the coarse-particle solid electrolyte is 5 μm to 50 μm, preferably 8 μm to 30 μm, and more preferably 10 μm to 20 μm. The average particle size of the fine-particle solid electrolyte is 0 μm to 10 μm. . 1 μm to 10 μm, preferably 0 μm . 5 μm to 5 μm, more preferably 1 μm to 3 μm, and even more preferably 1 μm . 5 μm to 2 μm.

[0059] The D10 of coarse-particle solid electrolytes is 1 μm to 10 μm, preferably 3 μm to 8 μm, and more preferably 4 μm. . 5 μm to 8 μm. The D90 of coarse-particle solid electrolytes is 30 μm to 100 μm, preferably 40 μm to 90 μm, more preferably 50 μm to 80 μm, and even more preferably 56 μm to 70 μm.

[0060] The D10 of fine-particle solid electrolytes is 0. . 1 μm to 5 μm, preferably 0 μm . 2 μm to 3 μm, more preferably 0 μm . The D90 of the fine-particle solid electrolyte is 1 μm to 20 μm, preferably 3 μm to 15 μm, and more preferably 5 μm to 15 μm.

[0061] The average particle size of sulfide-based solid electrolytes in the solid electrolyte layer can be larger than that in the cathode active material layer. Because coarse-particle solid electrolytes have a larger average particle size and fewer grain boundaries per unit volume, they can exhibit higher ionic conductivity when used in the solid electrolyte layer. When fine-particle solid electrolytes are used in the cathode active material layer, they can enter the voids between the cathode active material particles, thus providing lithium-ion conduction pathways for the cathode active material. Therefore, when the average particle size of sulfide-based solid electrolytes in the solid electrolyte layer is larger than that in the cathode active material layer, the discharge capacity and cycle characteristics of the all-solid-state battery can be improved.

[0062] Sulfide solid electrolytes may include any sulfur (S)-containing sulfide solid electrolytes commonly used in the art without particular limitation.

[0063] Sulfide solid electrolytes can have crystalline structures. Sulfide solid electrolytes with crystalline structures can accelerate lithium-ion conduction, thus exhibiting higher lithium-ion conductivity.

[0064] Sulfide solid electrolytes can have crystal structures of the argentite, nazonite, perovskite, garnet, or LGPS type. Preferably, the sulfide solid electrolyte has an argentite crystal structure. Because sulfide solid electrolytes with an argentite crystal structure exhibit excellent stability with lithium metal, they can facilitate the use of high-energy-density lithium metal as a negative electrode material.

[0065] Sulfide solid electrolytes can be in amorphous, glassy, ​​or glass-ceramic states.

[0066] Sulfide-based solid electrolytes may contain metals with ionic conductivity belonging to Group 1 or Group 2 of the periodic table, such as Li-PS-type glasses or Li-PS-type glass ceramics. Non-limiting examples of sulfide-based solid electrolytes may include at least one of Li₂S-P₂S₅, Li₂S-LiI-P₂S₅, Li₂S-LiI-Li₂O-P₂S₅, Li₂S-LiBr-P₂S₅, Li₂S-Li₂O-P₂S₅, Li₂S-Li₃PO₄-P₂S₅, Li₂S-P₂S₅-P₂O₅, Li₂S-P₂S₅-SiS₂, Li₂S-P₂S₅-SnS, Li₂S-P₂S₅-Al₂S₃, Li₂S-GeS₂, or Li₂S-GeS₂-ZnS, but sulfide-based solid electrolytes are not particularly limited thereto.

[0067] Sulfide-based solid electrolytes can contain crystalline and amorphous phases. They can contain a crystalline phase with a sulforaphite-germanium-type crystal structure (also referred to as the sulforaphite phase in this specification) and other phases (also referred to as impurity phases or unknown phases in this specification). Preferably, the sulforaphite-germanium-type crystal structure is cubic. The other phases can be crystalline or amorphous. These other phases can include crystalline or amorphous phases such as Li₂S, P₂S₅, LiCl, LiBr, Li₃PS₄, ZnS, CdS, and HgS. Preferably, the sulfide-based solid electrolyte contains almost no or no impurity phases other than the sulforaphite phase. That is, preferably, the sulfide-based solid electrolyte is entirely composed of the sulforaphite phase. When the sulfide-based solid electrolyte contains almost no or no impurity phases, lithium-ion conduction can be prevented, thus allowing for higher lithium-ion conductivity.

[0068] The proportion of crystalline phases in sulfide solid electrolytes can be quantitatively or semi-quantitatively assessed using XRD patterns. One assessment method involves calculating the proportion of crystalline phases by comparing peak intensities (peak heights or peak areas) in the XRD patterns.

[0069] Sulfide solid electrolytes can be made from the chemical formula Li 7-x-2y M y PS 6-x Ha x In the above chemical formula, M can be at least one element selected from Group 12, Ha can be at least one element selected from halogens, and 0... <x<2 . 5,0 <y<0 . 45. The lattice volume of sulfide solid electrolytes can be 940 Å. 3 Above and 980 Å 3 The following describes how sulfide-based solid electrolytes can exhibit high lithium-ion conductivity. When using sulfide-based solid electrolytes with high lithium-ion conductivity in anode-free all-solid-state batteries, the discharge capacity and cycle characteristics of the all-solid-state battery can be improved. Furthermore, because of this sulfide-based solid electrolyte with high lithium-ion conductivity, the growth of lithium dendrites on the negative electrode current collector can be suppressed, thereby enabling the anode-free all-solid-state battery of the present invention to operate under low confinement pressure.

[0070] In a sulfide-based solid electrolyte according to one embodiment of the present invention, Li 7-x PS 6-x Ha xIn this electrolyte, some lithium atoms are replaced by group 12 elements (M) capable of forming divalent cations. These group 12 elements (M) can include at least one selected from the group consisting of zinc (Zn), cadmium (Cd), and mercury (Hg). The ionic radius (6-coordinate) of lithium (Li) is 76 pm, while those of zinc (Zn), cadmium (Cd), and mercury (Hg) are 74 pm, 95 pm, and 102 pm, respectively. Depending on the valence state, one group 12 element (M) can replace two lithium atoms. Substitution of group 12 elements (M) can create lithium site vacancies, thereby improving lithium-ion conductivity. Furthermore, substitution of group 12 elements (M) can alter the lattice constant and lattice volume of sulfide-based solid electrolytes, forming crystal structures more suitable for lithium-ion conduction.

[0071] Furthermore, in one embodiment of the present invention, a sulfide-based solid electrolyte can be formed by intercalating a Group 12 element (M) capable of forming divalent cations into Li. 7-x PS 6-x Ha x The crystal is formed in a lattice manner. The Group 12 element (M) embedded in the lattice may include at least one selected from the group consisting of zinc (Zn) and cadmium (Cd), which may be used alone or in combination. Preferably, the Group 12 element (M) is zinc (Zn) and / or cadmium (Cd), with zinc (Zn) being particularly preferred. The Group 12 element (M) is inserted into Li... 7-x PS 6-x Ha x After modifying the crystal lattice, the lattice constant and lattice volume of the sulfide-based solid electrolyte can be changed to form a crystal structure suitable for lithium-ion conduction. Sulfide-based solid electrolytes containing zinc (Zn) as a Group 12 element (M) exhibit high lithium-ion conductivity. When this sulfide-based solid electrolyte is used in an anode-free all-solid-state battery, it can improve discharge capacity and cycle characteristics. Furthermore, using a sulfide-based solid electrolyte can prevent lithium dendrite growth on the negative electrode current collector, thereby enabling the anode-free all-solid-state battery of this invention to operate under low confinement pressure.

[0072] When the Group 12 element (M) is zinc (Zn) and / or cadmium (Cd), sulfide solid electrolytes can exhibit high crystallinity, thereby achieving high ionic conductivity. It is generally believed that because the ionic radius of lithium (Li) is similar to that of zinc (Zn) and cadmium (Cd), the substitution of lithium sites with Group 12 elements (M) can easily maintain the sulfide-germanium ore-type crystal structure.

[0073] In the chemical formula Li 7-x-2y M y PS 6-x Ha x In the equation, the content y of group 12 element (M) satisfies 0 <y<0. 45, preferably 0 <y<0 . 25, more preferably 0 <y<0 . 2, or even better, 0 <y<0 . 0.75, the optimal value is 0. . 0125≤y≤0 . 05. When y falls within the above range, sulfide solid electrolytes can exhibit high ionic conductivity. When y is 0, there is no crystal structure change due to substitution by group 12 elements (M), resulting in lower ionic conductivity. . Above 45, it may be impossible to maintain the sulfide-based solid electrolyte's sulfide-germanium ore-type crystal structure. Furthermore, impurity phases that hinder lithium-ion conduction increase in sulfide-based solid electrolytes, leading to lower ionic conductivity.

[0074] In the chemical formula Li 7-x-2y M y PS 6-x Ha x In this electrolyte, the halogen (Ha) includes at least one element selected from halogen elements. Preferably, it includes bromine (Br). More preferably, the halogen (Ha) includes chlorine (Cl) and bromine (Br). Sulfur (S) is a divalent anion, and its attraction to lithium ions is stronger than that of monovalent halogens, thus lithium ion migration may be significantly hindered. When bromine (Br) is included, the sulfur (S) occupancy at specific sites in the sulfide-germanium ore-type crystal structure decreases, the halogen occupancy at the corresponding sites increases, and the lithium ion migration near the bromine (Br) sites increases accordingly. As a result, the lithium-ion conductivity of the sulfide-based solid electrolyte can be improved. Furthermore, bromine (Br) can combine with Li in the sulfide-based solid electrolyte to form lithium bromide (LiBr). Lithium bromide (LiBr) absorbs moisture that leads to a decrease in lithium-ion conductivity, thereby improving the lithium-ion conductivity of the sulfide-based solid electrolyte.

[0075] In the chemical formula Li 7-x-2y M y PS 6-x Ha x In this case, the proportion of halogens (Ha) x satisfies 0. <x<2 . 5, preferably 1 . 0 <x<2 . 0, more preferably 1 . 3≤x≤2 . 0, or even more preferably 1 . 3≤x≤1 . 8. When x falls within the above range, a stable silver-germanium sulfide crystal structure can be achieved, and sulfide solid electrolytes can have high ionic conductivity.

[0076] The ionic conductivity of sulfide solid electrolytes can be affected by their crystallinity. Crystallinity can be assessed using X-ray diffraction (XRD) patterns. Sulfide solid electrolytes can exhibit high ionic conductivity when other phases besides the crystalline phase of argillium sulfide (crystalline or amorphous Li₂S, P₂S₅, LiCl, LiBr, Li₃PS₄, ZnS, CdS, and HgS phases are barely observable or not observed in the XRD pattern.

[0077] The lattice volume of sulfide-based solid electrolytes can be altered by substituting lithium sites with group 12 elements. Although not theoretically constrained, it is generally believed that due to the divalent cation properties of group 12 elements, strong interactions occur between these divalent cations and the anions present in sulfide-based solid electrolytes, leading to changes in the lattice volume (increase or decrease). These changes in lattice volume can create crystal structures suitable for lithium-ion conduction, thereby enabling sulfide-based solid electrolytes to exhibit high ionic conductivity.

[0078] The lattice volume of sulfide solid electrolytes is 940 Å. 3 Above and 980 Å 3 The following is preferred: 950 Å 3 Above and 970 Å 3 Hereinafter, 954 Å is more preferred. 3 Above and 966 Å 3 The lattice constant and lattice volume can be evaluated using XRD patterns. Even with the same composition, the lattice volume of sulfide solid electrolytes may vary with sintering temperature. When the lattice volume falls within the above range, lithium-ion conduction in sulfide solid electrolytes can be accelerated, thus allowing them to exhibit high ionic conductivity.

[0079] Unless otherwise stated, the ionic conductivity (also referred to as "lithium-ion conductivity" in this specification) of sulfide-based solid electrolytes refers to the ionic conductivity at room temperature (25°C, 298 K) and atmospheric pressure (1 atm). When sulfide-based solid electrolytes are used in all-solid-state batteries, the ionic conductivity in practical applications is preferably 4 mS / cm or higher. In one embodiment of the present invention, the ionic conductivity of the sulfide-based solid electrolyte can be 1 mS / cm. . 5 mS / cm or more, preferably 4 mS / cm or more, more preferably 8 mS / cm or more, and even more preferably 10 mS / cm or more. . The value is 8 mS / cm or higher, with the optimal value being 12 mS / cm or higher.

[0080] A sulfide-based solid electrolyte according to one embodiment of the present invention can be prepared by a manufacturing method comprising the following steps: mixing a lithium source, a group 12 element source, a phosphorus source, a sulfur source, and a halogen source to obtain a mixture, and sintering the mixture at a temperature of 250°C to 600°C. The sintering of the mixture can be carried out under an inert atmosphere such as argon or nitrogen.

[0081] The lithium source, group 12 element source, phosphorus source, sulfur source, and halogen source can include compounds such as sulfides, oxides, or nitrides. The lithium source can include lithium sulfide (Li₂S), the phosphorus source can include phosphorus pentasulfide (P₂S₅), and the halogen source can include lithium halides such as lithium chloride and lithium bromide. For example, the group 12 element source can include sulfides. Alternatively, sulfur can be supplied by a source of other elements. That is, at least one of the lithium source, group 12 element source, phosphorus source, or halogen source can act as the sulfur source.

[0082] In the case of sulfide solid electrolytes with a sulfide-germanium sulfide crystal structure, the sintering temperature is preferably 350°C to 550°C, more preferably 400°C to 500°C, and even more preferably 410°C to 470°C. When the sintering temperature falls within the above range, the formation of the sulfide-germanium sulfide crystal structure can be promoted, and the sulfide solid electrolyte can have high crystallinity. Thus, a sulfide solid electrolyte with high ionic conductivity can be obtained.

[0083] The solid electrolyte layer may also include an adhesive for the solid electrolyte layer. The adhesive for the solid electrolyte layer is added to bond the solid electrolyte together and anchor the battery components (such as the positive and negative electrodes) to the two surfaces of the solid electrolyte layer.

[0084] The adhesive for the solid electrolyte layer is not limited to a specific type and may include any suitable type within the selection range of adhesives for solid electrolytes in all-solid-state lithium secondary batteries. Specifically, the adhesive for the solid electrolyte layer may contain at least one selected from the group consisting of: polyvinylidene fluoride (PVdF), polyvinyl alcohol (PVA), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), styrene-butadiene rubber (SBR), styrene-butadiene-styrene block copolymer (SBS), nitrile rubber (NBR), fluororubber, and acrylic adhesives.

[0085] The solid electrolyte layer may also be without a binder for the solid electrolyte layer. When the solid electrolyte layer does not contain a binder for the solid electrolyte layer, the content of solid electrolyte in the solid electrolyte layer can be increased, thereby improving the ionic conductivity of the solid electrolyte layer.

[0086] <Negative electrode>

[0087] Before lithium metal is deposited during the first cycle (first charge), the negative electrode does not contain negative electrode active material.

[0088] During charging, lithium ions can be supplied by the positive electrode active material contained in the positive electrode active material layer, forming a lithium metal layer as the negative electrode active material on the negative electrode current collector. Specifically, when a predetermined voltage or higher is applied to charge an all-solid-state battery with an anode-free battery structure, lithium ions can be released from the positive electrode active material inside the positive electrode, and the released lithium ions can migrate through the solid electrolyte layer to the negative electrode current collector, forming a lithium metal layer on the negative electrode current collector, ultimately producing the negative electrode. Compared with conventional negative electrodes made by sputtering a lithium metal layer on the negative electrode current collector or stacking lithium foil with the negative electrode current collector, forming a lithium metal layer during charging can reduce the layer thickness and make the control of interface characteristics extremely simple.

[0089] In particular, the anode-free battery structure can reduce the risk of lithium metal being exposed to the atmosphere during battery assembly, thereby avoiding the formation of an oxide film on the surface due to the high reactivity of lithium and the resulting shortened lifespan of lithium secondary batteries.

[0090] The lithium metal layer forms a uniform, continuous, or discontinuous layer on the negative electrode current collector. When the negative electrode current collector is in foil form, a continuous thin film can be formed; when the negative electrode current collector has a three-dimensional porous structure, the lithium metal layer can be formed discontinuously. That is, the discontinuous layer can have the following distribution: a lithium metal layer is present in some locations within a specific region, while a lithium metal layer is absent in others; the distribution of lithium metal-free regions causes the lithium compound regions to appear as isolated, broken, or separated islands, reflecting the discontinuous distribution of the lithium metal layer regions.

[0091] To ensure the effective function of the negative electrode, the thickness of the lithium metal layer formed through charging and discharging can be at least 50 nm and less than 100 μm, preferably more than 1 μm and less than 50 μm. When the thickness is below the above range, the charge and discharge efficiency of the battery will drop sharply; conversely, when the thickness is above the above range, although the lifespan characteristics are stable, the energy density of the battery will decrease.

[0092] In particular, compared to conventional lithium secondary batteries assembled using lithium foil, in anode-free batteries that do not contain lithium metal during assembly, the lithium metal layer disclosed in this invention can hardly or completely avoid forming an oxide layer on the surface during the assembly process. This prevents battery life degradation caused by oxide layers.

[0093] In this invention, the charging region where the lithium metal layer is formed refers to the charging region in the 2... . 5V to 4 . Within a voltage range of 5 V, at 0 . 01C to 0 .A single charge cycle is performed at a charge / discharge rate of 2 C. When the charging parameters are below the above range, it is difficult to form a lithium metal layer; conversely, when the charging parameters are above the above range, it may cause battery damage, leading to over-discharge and thus preventing normal charge / discharge.

[0094] The negative electrode may include a negative electrode current collector. The negative electrode current collector is not limited to a specific type and may include any material that is conductive without causing chemical changes in the all-solid-state battery. The negative electrode current collector may include materials such as iron, stainless steel, aluminum, nickel, titanium, sintered carbon, or aluminum or stainless steel with a surface treated with carbon, nickel, titanium, or silver.

[0095] Specifically, the negative electrode current collector of the present invention is preferably non-reactive with the sulfide-based solid electrolyte. In other words, the all-solid-state battery of the present invention preferably does not contain reaction products between the negative electrode current collector and the sulfide-based solid electrolyte. The absence of reaction products between the negative electrode current collector and the sulfide-based solid electrolyte can be confirmed by observing the cross-section of the all-solid-state battery, for example, by scanning electron microscopy (SEM) or transmission electron microscopy (TEM). The absence of reaction products can be confirmed by XRD measurement. Before lithium metal is deposited during the first cycle (first charge), the negative electrode current collector and the sulfide-based solid electrolyte can be in direct contact. Furthermore, after the battery discharges, the lithium metal, as the negative electrode active material, migrates to the positive electrode, and the negative electrode active material is almost or completely absent on the negative electrode current collector. When a side reaction occurs between the negative electrode current collector and the sulfide-based solid electrolyte, byproducts such as hydrogen sulfide may be generated, which may adversely affect the performance of the all-solid-state battery. To suppress this side reaction, the negative electrode current collector preferably has high stability with the sulfide-based solid electrolyte. Since the negative electrode current collector does not react with the sulfide-based solid electrolyte, the anode-free all-solid-state battery of the present invention can have improved discharge capacity and cycle characteristics. Furthermore, because there are no by-reaction products between the negative electrode current collector and the sulfide-based solid electrolyte, the anode-free all-solid-state battery of the present invention can operate under low confinement pressure.

[0096] The thickness of the negative electrode current collector can be greater than 3 μm and less than 500 μm.

[0097] Negative current collectors can take different forms, such as membranes, sheets, foils, meshes, porous bodies, foams, or nonwoven fabrics with micro-textured surfaces.

[0098] The negative electrode current collector can directly contact the solid electrolyte layer. Specifically, it can directly contact the sulfide-based solid electrolyte contained within the solid electrolyte layer. When the negative electrode current collector directly contacts the solid electrolyte layer without an interlayer, the thickness of the all-solid-state battery can be reduced, thereby increasing its volumetric energy density. Furthermore, it can increase the loading of active materials and prevent lithium dendrite growth, thus improving the discharge capacity and cycle characteristics of the all-solid-state battery. Additionally, all-solid-state batteries can operate under low confinement pressure.

[0099] The negative electrode current collector may not be in direct contact with the solid electrolyte layer. An intermediate layer may exist between the negative electrode current collector and the solid electrolyte layer. In the presence of an intermediate layer, lithium ions supplied by the positive electrode active material layer migrate through the intermediate layer to the negative electrode current collector, forming a lithium metal layer on the negative electrode current collector. That is, during charging, a lithium metal layer is formed between the negative electrode current collector and the intermediate layer.

[0100] Here, the intermediate layer can contain any material capable of enabling rapid lithium-ion transport, including lithium-ion conductive polymers and / or materials for inorganic solid electrolytes. If necessary, the intermediate layer may also contain a lithium salt.

[0101] The intermediate layer may contain a metal that forms an alloy with lithium. The metal that forms an alloy with lithium may include germanium, tin, zinc, indium, gallium, antimony, lead, gold, silver, aluminum, platinum, or palladium.

[0102] Lithium-ion conductive polymers may include, for example, any one or a mixture thereof selected from polyethylene oxide (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVDF), and polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), but are not limited thereto; any polymer having lithium-ion conductivity may be used without restriction.

[0103] When lithium-ion conductive polymers are used, the intermediate layer may also contain materials to further improve lithium-ion conductivity.

[0104] For example, the intermediate layer may also contain lithium salts, such as LiCl, LiBr, LiI, LiClO4, LiBF4, and LiB. 10 Cl 10 LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, LiSCN, LiC(CF3SO2)3, (CF3SO2)2NLi, (FSO2)2NLi, lithium chloroborane, lower aliphatic carboxylic acids, lithium tetraphenylborate, or lithium imide.

[0105] Inorganic solid electrolytes can include ceramic-like crystalline or amorphous materials, such as thiolated LISICON (Li 3.25 Ge 0.25 P 0.75 S4), Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5, Li3PS4, Li7P3S 11 , Li2O-B2O3, Li2O-B2O3-P2O5, Li2O-V2O5-SiO2, Li2O-B2O3, Li3PO4, Li2O-Li2WO4-B2O3, LiPON, LiBON, Li2O-SiO2, LiI, Li3N, Li5La3Ta2O 12 Li7La3Zr2O 12 Li6BaLa2Ta2O 12 Li3PO (4-3 / 2w) N w (w < 1) or Li 3.6 Si 0.6 P 0.4 O4. In this case, when using an inorganic solid electrolyte, the intermediate layer may also contain a lithium salt if necessary.

[0106] Inorganic solid electrolytes can be mixed with known binders to prepare a slurry, which can then be coated to form a thick film. Alternatively, thin films can be formed via deposition processes such as sputtering, if necessary. The slurry coating method can be based on the specific circumstances mentioned in the section on lithium-ion conductive polymers, the appropriate selection of drying methods, and solvents.

[0107] An intermediate layer containing lithium-ion conductive polymers and / or inorganic solid electrolytes can improve the lithium-ion transport rate, facilitate the formation of a lithium metal layer, and suppress or prevent lithium dendrites when the lithium metal layer / anode current collector is used as the anode.

[0108] To achieve the above effect, the thickness of the intermediate layer needs to be limited.

[0109] A thinner interlayer thickness is more beneficial to the battery's output characteristics; however, when the interlayer thickness is less than a predetermined level, it is impossible to suppress subsequent lithium-electrolyte side reactions occurring on the negative electrode current collector, nor can it effectively prevent dendrite growth. In this invention, the thickness of the interlayer is preferably 10 nm or more and 50 μm or less. When the interlayer thickness is below the above range, it is impossible to effectively suppress the intensified side reactions and exothermic reactions between lithium and electrolyte under overcharging or high-temperature storage conditions, thus failing to improve safety; when the interlayer thickness is above the above range, the thickness of the all-solid-state battery increases, which may reduce the volumetric energy density of the all-solid-state battery.

[0110] Positive electrode

[0111] The positive electrode may include a positive electrode active material layer and a positive electrode current collector.

[0112] The positive electrode current collector is not limited to a specific type and can include any material with high conductivity that will not cause chemical changes in the positive electrode or battery. For example, it can include at least one material selected from the group consisting of iron, stainless steel, copper, aluminum, nickel, titanium, and sintered carbon, specifically aluminum. The positive electrode current collector may contain carbon-based conductive materials and a binder, and may also contain a base coating applied to the surface of the positive electrode current collector. This significantly improves the adhesion and conductivity between the positive electrode active material layer and the current collector.

[0113] The positive electrode active material layer can be disposed on at least one surface of the positive electrode current collector. Specifically, the positive electrode active material layer can be disposed on one or both surfaces of the positive electrode current collector.

[0114] The positive electrode active material layer may contain a positive electrode active material. In the anode-free battery structure of the present invention, the lithium forming the lithium metal layer is derived from the positive electrode active material, and the positive electrode active material contains lithium. In other words, during charging within a specific voltage range, lithium ions released from the positive electrode active material will form a lithium metal layer on the negative electrode current collector.

[0115] The positive electrode active material is not limited to a specific type and can include any positive electrode active material used in lithium-ion secondary batteries. Positive electrode active materials can include, but are not limited to: layered compounds comprising lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2), or compounds substituted with one or more transition metals; with the chemical formula Li 1+x Mn 2-x O4 (x is 0 to 0) . 33) Lithium manganese oxides of LiMnO3, LiMn2O3, LiMn2O4 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiV3O4, V2O5, Cu2V2O7; and LiNi 1-x M x O2(M=Co, Mn, Al, Cu, Fe, P, Mg, Ca, Zr, Ti, Ru, Nb, W, B, Si, Na, K, Mo, V or Ga, x=0 . 01 to 0 . 3) Represents a Ni-site type lithium nickel oxide; its chemical formula is LiMn 1-x M x O2(M=Co, Ni, Fe, Cr, Zn or Ta, x=0 . 01 to 0 .1) or Li2Mn3MO8 (M = Fe, Co, Ni, Cu or Zn) represents lithium manganese composite oxides; LiNi x Mn 2-x O4 represents spinel-type lithium-manganese composite oxides; LiMn2O4 in which part of the Li is replaced by alkaline earth metal ions; disulfides; LiMn x Fe 1-x PO4(0≤x≤0 . 9); Fe2(MoO4)3.

[0116] Positive electrode active materials may include Li 1+x M y O 2+ z and M can be at least one element selected from the group consisting of Ni, Co, Mn, Fe, P, Al, Mg, Ca, Zr, Zn, Ti, Ru, Nb, W, B, Si, Na, K, Mo, and V, and 0 ≤ x ≤ 5, 0 < y ≤ 2, and 0 ≤ z ≤ 2. Specifically, Li 1+x M y O 2+ z may include at least one selected from the group consisting of: LiCoO2, LiNiO2, LiMnO2, Li[Ni 0.5 Co 0.3 Mn 0.2 O2, Li[Ni 0.6 Co 0.2 Mn 0.2 O2, Li[Ni 0.7 Co 0.1 Mn 0.2 O2, Li[Ni 0.8 Co 0.1 Mn 0.1 O2, Li[Ni 0.9 Co 0.05 Mn 0.05 O2, LiMn2O4, LiFePO4 and 0.5 Li2MnO 3·0.5 Li[Mn 0.4 Ni 0.3 Co 0.3 O2. Preferably, Li 1+x M y O 2+ z can include Li[Ni] 0.6 Co 0.2 Mn 0.2 O2, Li[Ni 0.7 Co 0.1 Mn 0.2 O2, Li[Ni 0.8 Co 0.1Mn 0.1 ]O2 and Li[Ni 0.9 Co 0.05 Mn 0.05 Any of the following: O2. Because the positive electrode active material contains Li... 1+x M y O 2+ z, therefore, sufficient lithium can be supplied to the negative electrode, and because Li 1+x M y O 2+ z exhibits electrochemical activity after the first cycle and does not cause battery performance degradation, thus avoiding battery capacity decay caused by the irreversible capacity of the negative electrode. 1+x M y O 2+ z can be a secondary particle morphology formed by primary particle aggregation or agglomeration, or it can be a single particle morphology.

[0117] The content of the positive electrode active material in the positive electrode active material layer can be from 50% to 95% by weight, specifically from 60% to 90% by weight.

[0118] Furthermore, the average particle size of the positive electrode active material is 1 μm or more and 30 μm or less, and according to one embodiment, it can be 8 μm or more and 12 μm or less. When the average particle size of the positive electrode active material falls within the above range, the capacity characteristics of the battery can be improved.

[0119] The positive electrode active material layer may also contain a positive electrode conductive material.

[0120] The positive electrode conductive material is not limited to a specific type and can include any material that is conductive without causing chemical changes in the positive electrode or battery. For example, it can include one selected from the following: graphite, including natural graphite or artificial graphite; carbon black, including carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal cracking carbon black; graphene; conductive fibers, including carbon nanofibers and carbon nanotubes; fluorocarbons; metal powders, including aluminum powder and nickel powder; conductive whiskers, including zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, including titanium oxide; polyphenylene derivatives, or mixtures thereof.

[0121] The content of positive electrode conductive material in the positive electrode active material layer can be from 1% to 30% by weight.

[0122] The positive electrode active material layer may also include a positive electrode binder.

[0123] The positive electrode adhesive is not limited to a specific type and can include any material that facilitates the adhesion of the positive electrode active material to the positive electrode conductive material and its bonding with the current collector. Specifically, the positive electrode adhesive can include at least one selected from the group consisting of: polyvinylidene fluoride (PVdF), polyvinyl alcohol (PVA), carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, polyvinylpyrrolidone, polytetrafluoroethylene (PTFE), polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), styrene-butadiene rubber (SBR), and fluororubber.

[0124] The content of the positive electrode binder in the positive electrode active material layer can be from 1% to 30% by weight.

[0125] If necessary, the positive electrode active material layer may contain at least one additive selected from oxidation stabilizing additives, reduction stabilizing additives, flame retardants, heat stabilizers, or antifogging agents.

[0126] The positive electrode active material layer may also contain a sulfide-based solid electrolyte. The sulfide-based solid electrolyte contained in the positive electrode active material layer may have the same composition as the sulfide-based solid electrolyte contained in the solid electrolyte layer, or it may have a different composition.

[0127] The content of sulfide solid electrolyte in the positive electrode active material layer can be from 5% to 60% by weight, specifically from 10% to 40% by weight.

[0128] The average particle size of the positive electrode active material can be larger than the average particle size of the solid electrolyte particles contained in the positive electrode active material layer. In this case, the solid electrolyte particles can enter the gaps between the positive electrode active material particles, thereby providing a lithium-ion conduction path for the positive electrode active material.

[0129] This invention provides a secondary battery having the above-described structure. Furthermore, this invention also provides a battery module comprising the secondary battery as a unit cell, a battery pack comprising the battery module, and a device comprising the battery pack as a power source. In this context, specific examples of the device may include, but are not limited to, any type of device driven by an electric motor, such as power tools; electric vehicles including electric vehicles (EVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs); two-wheeled electric vehicles including electric bicycles or electric scooters; electric golf carts; or electrical systems.

[0130] The following description of embodiments is intended to illustrate the invention. However, the embodiments described below are merely illustrative of the invention, and it is obvious that those skilled in the art can make their own modifications and alterations within the scope of the invention, and such modifications and alterations clearly fall within the scope of the appended claims.

[0131] (Synthesis of solid electrolytes)

[0132] Preparation Example 1

[0133] Weigh out the raw materials lithium sulfide (Li₂S, Mitsuwa Chemical), phosphorus pentasulfide (P₂S₅, Aldrich), zinc sulfide (ZnS, Japan Pure Chemical), lithium chloride (LiCl, Aldrich), and lithium bromide (LiBr, Aldrich), and mix them in a mortar and pestle in an Ar gas glove box to meet the requirements of Li 5.4-2y M y PS 4.4 Cl 1.0 Br 0.6 (The content of element M in group 12 is y=0) . The composition of 025) was used to obtain a powder mixture. This powder mixture was then placed in a ZrO2 container along with ZrO2 balls and sealed. The sealed container was mounted on a planetary ball mill, and the mixture was ball-milled at 380 rpm for 20 hours. The powder was collected inside the glove box. The collected powder was placed in a carbon crucible and sealed, and sintered at 430°C for 8 hours while Ar gas was introduced. The sintered powder was then ground in a mortar for 10 minutes to obtain a coarse-particle solid electrolyte containing divalent cations of zinc, a group 12 element.

[0134] Preparation Example 2

[0135] The coarse-particle solid electrolyte containing divalent cations obtained in Preparation Example 1 was placed in a ZrO2 container along with ZrO2 balls and anisole solvent, and wet-milled at 250 rpm for 1 hour to obtain a fine-particle solid electrolyte containing divalent cations.

[0136] Comparative Preparation Example 1

[0137] A coarse-particle solid electrolyte without divalent cations was obtained in the same manner as in Preparation Example 1, except that zinc sulfide (ZnS, a product of Japan Pure Chemical) was not used. The solid electrolyte obtained in Preparation Example 1 had a composition of Li. 5.4 PS 4.4 Cl 1.0 Br 0.6 .

[0138] Comparative Preparation Example 2

[0139] The coarse-particle solid electrolyte without divalent cations obtained in Comparative Preparation Example 1 was placed in a ZrO2 container along with ZrO2 balls and anisole solvent, and wet-milled at 250 rpm for 1 hour to obtain a fine-particle solid electrolyte without divalent cations.

[0140] Comparative Preparation Example 3

[0141] The coarse-particle solid electrolyte containing divalent cations obtained in Preparation Example 1 was placed in a ZrO2 container along with ZrO2 balls and anisole solvent, and wet-milled at 250 rpm for 5 hours to obtain a fine-particle solid electrolyte containing divalent cations.

[0142] evaluate

[0143] The obtained solid electrolyte was evaluated as follows.

[0144] (XRD measurement)

[0145] Inside an Ar gas glove box, a predetermined amount of solid electrolyte was placed on an airtight, sealed sample stage for XRD analysis. The lattice constant, lattice volume, and full width at half maximum (FWHM) were calculated from the obtained XRD patterns. The FWHM is determined by... Figure 4 The diffraction peaks of the (311) crystal plane of the sulfosilver-germanium type crystal structure observed near 2θ=30° were calculated.

[0146] The measuring equipment and conditions are as follows: • X-ray diffraction apparatus: Rigaku Smartlab • Radiation source: Cu-Kα radiation (λ=1) . 5418 Å) • Voltage: 45kV • Current: 200mA • Scan range (2θ): 10°-60° • Step size: 0 . 01° (Particle size distribution determination) A solid electrolyte was added to heptane solvent, and Span 80 was used as a dispersant to prepare a solid electrolyte dispersion. The particle size distribution was measured using a Mastersizer 3000 particle size distribution analyzer. For data analysis, the refractive index of the solid electrolyte was taken as 2. . 16.

[0147] (Measurement of ionic conductivity)

[0148] The predetermined amount of solid electrolyte was loaded into MACOR. ® In the tube, MACOR ®The tube is assembled with a pellet forming fixture (upper and lower pressure needles) and pressed using a uniaxial press at approximately 370 MPa. A predetermined amount of gold powder is then placed on both sides of the pellet, and it is pressed again using a uniaxial press at approximately 554 MPa to obtain the MACOR® tube cell. The resulting MACOR® tube cell is installed in a cell holder for electrochemical measurement, and a pressure of up to 80 MPa is applied using a torque wrench to obtain a cell for ionic conductivity measurement. This ionic conductivity measurement cell is connected to an impedance measuring device, and the resistance of the solid electrolyte pellet is measured at room temperature (298 K) and atmospheric pressure (1 atm) to calculate the ionic conductivity of the solid electrolyte.

[0149] Evaluation results

[0150] (Crystal phase)

[0151] Table 1 summarizes the evaluation results of the crystal phase (crystal structure) identified by XRD patterns obtained through XRD determination. Figure 4 The measured XRD patterns are shown in Table 1. Figure 4 It can be seen that in the solid electrolytes obtained from Preparation Example 1, Preparation Example 2, Comparative Preparation Example 1, and Comparative Preparation Example 2, almost no impurity phases (also called unknown phases) were observed, and only diffraction peaks of the argyrogermanium sulfide phase were observed. Sulfide-based solid electrolytes with an argyrogermanium sulfide crystal structure and almost no or completely free of impurity phases were obtained. Sulfide-based solid electrolytes with high crystallinity can promote the hopping conduction of lithium ions, thereby helping to improve ionic conductivity.

[0152] Table 1

[0153] (Lattice volume)

[0154] In Preparation Example 1 and Preparation Example 2, the lattice constant obtained from the XRD patterns was 9. . 8750 Å to 9 . 8755 Å, lattice volume 962 . 9 Å 3 Up to 963 . 1 Å 3 Meanwhile, in Comparative Preparation Example 1 and Comparative Preparation Example 2, where lithium sites were not substituted with Group 12 elements (M), the lattice constant was 9. . 9467 Å to 9 . 9470 Å, lattice volume 984 . 1 Å 3 Up to 984 . 2 Å 3 It was confirmed that substituting lithium sites in a sulforaphane-germanium-type crystal structure with a group 12 element (M) reduced the crystal volume by approximately 2%. .1%. Although not theoretically constrained, it is generally believed that the change in crystal volume of sulfide solid electrolytes stems from the substitution of one of the two lithium sites by a Group 12 element (M), leaving the other vacant (lithium vacancy). This lithium vacancy is thought to act as a pathway for lithium-ion hopping conduction, contributing to improved ionic conductivity. Furthermore, since the Group 12 element (M) substituting the lithium site is divalent, its attraction to anions near the Group 12 element (M) site may differ compared to monovalent lithium ions. Therefore, it is generally believed that the change in crystal volume of sulfide solid electrolytes leads to a structure suitable for lithium-ion hopping conduction.

[0155] The full width at half maximum (FWHM) of the diffraction peaks on the (311) crystal plane of the sulfogermanite-type crystal structure was 0 in Preparation Example 1 and Preparation Example 2. . 0.6°, which is 0 in Comparative Preparation Example 1 and Comparative Preparation Example 2. . 08°. In Preparation Examples 1 and 2 (i.e., solid electrolytes containing divalent cations), the full width at half maximum (FWHM) was small. It is generally believed that a smaller FWHM corresponds to a larger grain size, which helps to improve ionic conductivity. At the same time, it was confirmed that the morphological change of the solid electrolyte from coarse to fine particles does not change the crystallinity and grain size of the solid electrolyte.

[0156] (Particle size distribution)

[0157] Table 2 summarizes the particle size distribution determination results. The average particle size D50 of the coarse-particle solid electrolyte containing divalent cations in Preparation Example 1 was 15. . 6 μm; the average particle size D50 of the fine-particle solid electrolyte containing divalent cations in Preparation Example 2 was 1 μm. . 68 μm. Furthermore, the average particle size D50 of the coarse-particle solid electrolyte without divalent cations in Comparative Preparation Example 1 was 14 μm. . 7 μm; compared to the fine-particle solid electrolyte without divalent cations in Preparation Example 2, the average particle size D50 was 1. . 42 μm. This confirms that the morphological change of solid electrolytes from coarse to fine particles can be achieved by additional wet milling. Furthermore, the average particle size D50 of the fine-particle solid electrolyte containing divalent cations in Comparative Preparation Example 3 is 1. . 2 μm.

[0158] The D10 of the coarse-particle solid electrolyte containing divalent cations in Preparation Example 1 is 4. . 85 μm; the D10 of the fine-particle solid electrolyte containing divalent cations in Preparation Example 2 is 0. . 71 μm. Furthermore, the D10 of the coarse-particle solid electrolyte without divalent cations in Preparation Example 1 was 4. . 0.3 μm; the D10 of the fine-particle solid electrolyte without divalent cations in Preparation Example 2 is 0.. 73 μm. Furthermore, the D10 of the fine-particle solid electrolyte containing divalent cations in Preparation Example 3 was 0. . 71 μm.

[0159] The D90 of the coarse-particle solid electrolyte containing divalent cations in Preparation Example 1 was 59. . 2 μm; the D90 of the fine-particle solid electrolyte containing divalent cations in Preparation Example 2 is 5. . 0.9 μm. Furthermore, the D90 of the coarse-particle solid electrolyte without divalent cations in Preparation Example 1 was 55. . 7 μm; the D90 of the fine-particle solid electrolyte without divalent cations in Preparation Example 2 is 4. . 86 μm. Furthermore, the D90 of the fine-particle solid electrolyte containing divalent cations in Preparation Example 3 was 3. . 0.9 μm.

[0160] Table 2

[0161] (ionic conductivity)

[0162] Table 1 summarizes the results of the ionic conductivity measurements. The ionic conductivity of the coarse-particle solid electrolyte containing divalent cations in Preparation Example 1 was 12. . 98 mS / cm; the ionic conductivity of the fine-particle solid electrolyte containing divalent cations in Preparation Example 2 was 4. . 30 mS / cm. Furthermore, the ionic conductivity of the coarse-particle solid electrolyte without divalent cations in Preparation Example 1 was 9. . 91 mS / cm; the ionic conductivity of the fine-particle solid electrolyte without divalent cations in Preparation Example 2 was 3. . 3 mS / cm. Furthermore, the ionic conductivity of the fine-particle solid electrolyte containing divalent cations in Preparation Example 3 was 2. . 5 mS / cm. Regardless of the presence or absence of divalent cations, coarse-particle solid electrolytes exhibit higher ionic conductivity than fine-particle solid electrolytes. It is generally believed that coarse-particle solid electrolytes result in higher ionic conductivity due to fewer grain boundaries per unit volume. Regardless of the average particle size of the solid electrolyte, solid electrolytes containing divalent cations have higher ionic conductivity than those without. Even with divalent cations, excessively small particle sizes of the solid electrolyte can lead to impurities and a decrease in ionic conductivity.

[0163] Example 1

[0164] Weigh 90 mg of the coarse-particle solid electrolyte containing divalent cations obtained in Preparation Example 1, load it into a molding fixture, and pressurize it at 110 MPa for 1 minute to obtain solid electrolyte pellets.

[0165] An NCM-type positive electrode active material with a nickel content of 80 mol%, a fine-particle solid electrolyte containing divalent cations obtained in Preparation Example 2, and a conductive material were weighed in a mass ratio of 60:35:5. These were then mixed to obtain a positive electrode mixed material.

[0166] 17 mg of the above-mentioned positive electrode mixture was placed on one side of a solid electrolyte pellet and flattened using a SUS pressure needle in a molding jig. The pellet was then pressed at 110 MPa for 1 minute to form a positive electrode active material layer on the solid electrolyte layer. An SUS plate serving as the positive electrode current collector was placed on the positive electrode active material layer, and an SUS plate serving as the negative electrode current collector was placed in direct contact with the solid electrolyte layer on the side opposite to the positive electrode active material layer. The pellet was then pressed at 554 MPa for 1 minute to obtain a laminate. The resulting laminate was then combined with the SUS pressure needle to manufacture a MACOR. ® Tube cell. MACOR ® The tubular cells are installed in the battery cell, and approximately 0 are applied. . A low confinement pressure of 1 MPa yields an all-solid-state battery. Specifically, the all-solid-state battery of Example 1 contains a coarse-particle solid electrolyte with divalent cations in the solid electrolyte layer and a fine-particle solid electrolyte with divalent cations in the positive electrode active material layer.

[0167] Figure 1 The all-solid-state battery of Example 1 is shown. For example... Figure 1 As shown, the negative electrode current collector 1 is in direct contact with the solid electrolyte layer 2, which contains a solid electrolyte with divalent cations. The all-solid-state battery of Example 1 is in a battery precursor state before the initial charge and does not have a negative electrode active material layer. The all-solid-state battery of Example 1 is an anode-less all-solid-state battery. During charging and discharging, lithium is deposited and dissolved between the negative electrode current collector 1 and the solid electrolyte layer 2, thereby enabling the battery to function.

[0168] Comparative Example 1

[0169] An all-solid-state battery was obtained in the same manner as in Example 1, except that the coarse-particle solid electrolyte containing divalent cations used to prepare the solid electrolyte pellets was replaced with the coarse-particle solid electrolyte without divalent cations obtained in Comparative Preparation Example 1, and the fine-particle solid electrolyte containing divalent cations used to prepare the cathode hybrid material was replaced with the fine-particle solid electrolyte without divalent cations obtained in Comparative Preparation Example 2. That is, as Figure 2As shown, the all-solid-state battery of Comparative Example 1 contains a coarse-particle solid electrolyte without divalent cations in the solid electrolyte layer and a fine-particle solid electrolyte without divalent cations in the positive electrode active material layer.

[0170] Comparative Example 2

[0171] An all-solid-state battery was obtained in the same manner as in Example 1, except for the following preparation steps: An Ag-C interlayer was formed on the side of the solid electrolyte layer opposite to the positive electrode active material layer; an SUS plate, serving as the negative electrode current collector, was placed on the interlayer, and a constraint pressure of approximately 4 MPa was applied. The Ag-C interlayer was formed by dissolving a predetermined amount of Ag and carbon black in a mixture containing 7% by weight of PVDF in N-methylpyrrolidone, and then coating it onto the SUS plate. That is, as... Figure 3 As shown, the all-solid-state battery of Comparative Example 2 contains a coarse-particle solid electrolyte without divalent cations in the solid electrolyte layer, and a fine-particle solid electrolyte without divalent cations in the positive electrode active material layer, and an intermediate layer is provided between the solid electrolyte layer and the negative electrode current collector.

[0172] Evaluation of all-solid-state batteries

[0173] (Charge / Discharge Test)

[0174] The obtained all-solid-state battery was used to conduct charge-discharge tests at 25°C. The voltage range was 4... . 25V to 3 . The charging condition was CC (0.05C)-CV (0.01C cutoff), and the discharging condition was CC (0.05C). The charging and discharging capacities were calculated from the charge-discharge curves. Furthermore, the discharge capacity retention rate (%) under the charging conditions of 25℃ and CC (0.05C)-CV (0.01C) and the discharging conditions of CC (0.05C) was obtained using the following formula: Discharge capacity of each cycle / discharge capacity of the first cycle × 100 Evaluation results (Characteristics of all-solid-state batteries) The ratio of the initial discharge capacity of the all-solid-state battery of Example 1 to that of the all-solid-state battery of Comparative Example 1 is 101%. As described above, compared with the all-solid-state battery of Comparative Example 1 which does not contain the sulfide-based solid electrolyte of the present invention, the all-solid-state battery of Example 1, which contains a sulfide-based solid electrolyte layer containing a Group 12 element and having a sulfide-germanium ore-type crystal structure, can have a higher discharge capacity.

[0175] Figure 5 The graph shows the discharge capacity retention rate of the all-solid-state batteries of Example 1, Comparative Example 1, and Comparative Example 2.

[0176] The discharge capacity retention rate after the third cycle was 99% in Example 1. . 4%, compared to 78% in Comparative Example 1. . 8%, compared to 92% in Comparative Example 2. . 4%.

[0177] The discharge capacity retention rate after the 7th cycle was 98% in Example 1. . 6%, compared to 85% in Comparative Example 2. . 7%. In Comparative Example 1, the discharge capacity decreased sharply after 4 cycles, making it impossible to measure the discharge capacity. Compared to Comparative Example 1, Comparative Example 2 has an intermediate layer 6 between the solid electrolyte layer 5 and the negative electrode current collector 1. It is speculated that Comparative Example 2 has improved cycle characteristics compared to Comparative Example 1 because the intermediate layer 6 suppresses the growth of lithium dendrites.

[0178] As described above, compared with the all-solid-state batteries of Comparative Examples 1 and 2 which do not contain the sulfide-type solid electrolyte of the present invention, the all-solid-state battery of Example 1, which contains a sulfide-type solid electrolyte with a group 12 element and has a sulfide-germanium sulfide crystal structure, can have improved cycle characteristics.

[0179] The all-solid-state battery of Example 1 contains a coarse-particle solid electrolyte with divalent cations in the solid electrolyte layer (i.e., the coarse-particle solid electrolyte of Preparation Example 1); the all-solid-state battery of Comparative Example 1 contains a coarse-particle solid electrolyte without divalent cations in the solid electrolyte layer (i.e., the coarse-particle solid electrolyte of Comparative Preparation Example 1). As shown in Table 1, the ionic conductivity of the coarse-particle solid electrolyte of Preparation Example 1 is approximately 1 / 3 that of the coarse-particle solid electrolyte of Comparative Preparation Example 1. . 3 times. For example... Figure 5 As shown, compared with the all-solid-state battery of Comparative Example 1, the all-solid-state battery of Example 1 has improved cycle characteristics. It is generally believed that the improved cycle characteristics of the all-solid-state battery of Example 1 are due to the high ionic conductivity of the coarse-particle solid electrolyte containing divalent cations.

[0180] Furthermore, during the charging and discharging process of all-solid-state batteries, high confinement pressure is typically required to suppress the growth of lithium dendrites on the negative electrode current collector. However, if... Figure 5 As shown, compared to the all-solid-state battery of Comparative Example 2, which was subjected to a high confinement pressure of approximately 4 MPa, the battery subjected to approximately 0 MPa... . The all-solid-state battery of Example 1, with a low confinement pressure of 1 MPa, exhibits improved cycle characteristics. It is generally believed that the improved cycle characteristics of the all-solid-state battery of Example 1 are due to the use of a solid electrolyte layer containing divalent cations in both the solid electrolyte layer and the positive electrode active material layer. As described above, the all-solid-state battery of the present invention can operate under low confinement pressure.

[0181] Although the present invention has been described above with reference to several embodiments and accompanying drawings, the present invention is not limited thereto. It is evident that those skilled in the art to which this invention pertains can make various modifications and alterations within the technical scope of the present invention and the appended claims and their equivalents.

[0182] [Figure Labels]

[0183] 1: Negative electrode current collector

[0184] 2: Solid electrolyte layer containing divalent cations

[0185] 3: Positive electrode active material layer

[0186] 4: Positive current collector

[0187] 5: Solid electrolyte layer of solid electrolyte without divalent cations

[0188] 6: Intermediate layer

Claims

1. An all-solid-state battery, comprising: The all-solid-state battery comprises a positive electrode with a positive active material layer, a negative current collector, and a solid electrolyte layer disposed between the positive electrode and the negative current collector, wherein the all-solid-state battery does not contain a negative active material. During charging, lithium ions are supplied by the positive electrode active material layer, and a lithium metal layer serving as the negative electrode active material is formed on the negative electrode current collector. The solid electrolyte layer comprises a sulfide solid electrolyte containing elements of Group 12, and the sulfide solid electrolyte has a sulfogermanium ore-type crystal structure.

2. The all-solid-state battery as described in claim 1, in, The negative electrode current collector is in direct contact with the solid electrolyte layer.

3. The all-solid-state battery as described in claim 1, in, The sulfide solid electrolyte is composed of the chemical formula Li 7-x-2y M y PS 6-x Ha x In this representation, M is at least one element selected from Group 12, Ha is at least one element selected from halogens, and 0 <x<2 . 5,0 <y<0 .

45.

4. The all-solid-state battery as described in claim 3, in, M is Zn.

5. The all-solid-state battery as described in claim 1, in, The all-solid-state battery does not contain the reaction products of the negative electrode current collector and the sulfide-based solid electrolyte.

6. The all-solid-state battery as described in claim 1, in, A 0°C pressure is applied to the all-solid-state battery along the stacking direction of the positive electrode, the negative electrode current collector, and the solid electrolyte layer. . Pressure below 3 MPa.

7. The all-solid-state battery as described in claim 1, in, The positive electrode active material layer contains the sulfide-based solid electrolyte.

8. The all-solid-state battery as described in claim 1, in, The solid electrolyte has a D10 of 0. . 1 μm to 10 μm.

9. The all-solid-state battery as described in claim 1, in, The solid electrolyte has a D50 of 0. . 1 μm to 50 μm.

10. The all-solid-state battery as described in claim 1, in, The solid electrolyte has a D90 of 1 μm to 100 μm.

Citation Information

Patent Citations

  • All-solid type secondary battery, and manufacturing method, using method and charging method thereof

    JP2020167146A

  • All-solid-state lithium secondary battery

    JP2020191202A

  • Methods of Making and Using Electrochemical Cells Including Interlayers

    JP2022504134A

  • Electrolyte membrane for all-solid-state battery and all-solid-state battery including the same

    JP2022529975A